IgE is expressed on, but not produced by, fetal cells in the human placenta irrespective of maternal atopy - EKSTRÖM, E SVERREMARK (Blackwell Science Inc, 2002)
The prevalence of atopic diseases in children has increased during the last decades. Atopic symptoms usually appear early in life. This implies an early priming for atopic disease, possibly even at the fetal level. We therefore compared the presence and production of IgE in the local in utero environment during pregnancy in atopic and non-atopic women. Eighty-six women were included in the study. Fifty women were demonstrated to be atopics, based on clinical symptoms of atopic disease together with a positive Phadiatop and/or skin prick test. Placentas from these term pregnancies were obtained. Slices covering the full thickness of the placenta were cut clockwise around the umbilical cord and were analysed with immunohistochemistry. Surprisingly, numerous IgE(+) cells, located primarily in the fetal villous stroma, were detected in a majority of the investigated placentas irrespective of the atopy of the mother or maternal or fetal total serum IgE levels. The placental IgE could not be demonstrated to be bound to IgE receptors, but was shown to be bound to fetal macrophages, possibly via FcγRI. No evidence was found for local fetal IgE production, although cells producing epsilon transcripts were occasionally detected in the decidua. We describe here the novel finding of numerous IgE(+) cells in the human placenta, suggesting an hitherto unknown role for IgE in a successful pregnancy outcome, irrespective of whether or not the mother is atopic.